Pengaruh Destination Image, Fasilitas dan Harga Terhadap Keputusan Berkunjung Wisatawan Eco Park Syariah Tan Kayo Batipuh Selatan - Wadriman, Wadriman; Hayati, Annur Fiitri (Jurnal Ecogen, 2024)
This study is to examine the impact of prices, amenities, and destination image on travelers' decisions to visit Eko Park Syariah Tan Kayo South Batipuh. This kind of investigate is known as research that is causal. Tourists who went to the Eko Park Syariah Tan Kayo South Batipuh tourist attraction made up the study's population. The Chocran formula, which calls for 100 samples, is used to determine the sample size. The puroposive sampling strategy is employed in this study. Primary data meeting predefined criteria is what is used. Using SPSS 25, multiple regression analysis is the analytical technique employed. The findings of the study indicate that (1) Traveling decisions are significantly influenced by destination image, amenities, and prices. (2) Decisions about visiting are significantly influenced by the destination image. (3) Decisions on visiting are significantly influenced by facilities. (4) The price of a visit has an important effect on decisions.